Bone Anatomy of the Thoracic Limb in the Common Hippopotamus (Hippopotamus amphibius) and White Rhinoceros (Ceratotherium simum) - Gallina, Pedro Leonardo Sangaleti [UNESP]; Schimming, Bruno Cesar [UNESP] (Soc Chilena Anatomia, 2023)
Although megaherbivores do not belong to the Brazilian fauna, they can be found in national zoos, which makes it important to know the anatomy of the locomotor apparatus to contribute to the clinical routine of zoos and veterinary rehabilitation centers. Thus, the aim of this study was to describe the anatomical structures of the thoracic limb bones in the common hippopotamus (Hippopotamus amphibius) and white rhinoceros (Ceratotherium simum) and to compare them with the bone structures described for other ungulates. The scapula had a triangular appearance in the common hippopotamus, whereas in the white rhinoceros it had a rectangular appearance. The acromion was observed only in the common hippopotamus scapula. The hippopotamus humerus did not have the intermediate tubercle, only the greater and lesser tubercles, unlike the rhinoceros which also has the intermediate tubercle. The two megamammals studied had an ulna not incorporated to the radius and seven carpal bones distributed in two bone rows. The common hippopotamus had four digits and four metacarpal bones, while the white rhino had three digits, hence three metacarpal bones. Although with some species-specific differences, the bone anatomy found in the studied megaherbivores was similar to that described for domestic ungulates, such as horses and cattle. The fact that the bones studied belong to articulated skeletons of the collection of the Museum of Anatomy made it difficult to identify some anatomical structures. This study can help veterinarians in bone health care, animal welfare and comfort of such species present in Brazilian zoological parks.
Keywords: Hippopotamus; Megaherbivores; Osteology; Rhino; Thoracic limb